2016
DOI: 10.1002/aur.1637
|View full text |Cite
|
Sign up to set email alerts
|

Personal space regulation in childhood autism: Effects of social interaction and person's perspective

Abstract: Studies in children with Typical Development (TD) and with Autism Spectrum Disorder (ASD) revealed that autism affects the personal space regulation, influencing both its size (permeability) and its changes depending on social interaction (flexibility). Here, we investigate how the nature of social interaction (Cooperative vs. Uncooperative) and the person perspective influence permeability and flexibility of interpersonal distance. Moreover, we tested whether the deficit observed in ASD children, reflects the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 34 publications
9
58
0
Order By: Relevance
“…Indeed, an array of recent observations indicates that PPS is not only heavily influenced by external or environmental conditions, but also by personality traits such as anxiety (Sambo and Iannetti, 2013) or claustrophobia (Lourenco et al, 2011). Similarly, theoretical postulations suggest that the representation of PPS may play an under-appreciated role in psychopathology (Candini et al, 2017;Noel et al, 2017). Thus, the results reported here suggest that function fitting coupled with immersion in a realistic environment and the presentation of multiple cues of information pertaining to the external environment may be best suited for future individual differences studies of PPS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an array of recent observations indicates that PPS is not only heavily influenced by external or environmental conditions, but also by personality traits such as anxiety (Sambo and Iannetti, 2013) or claustrophobia (Lourenco et al, 2011). Similarly, theoretical postulations suggest that the representation of PPS may play an under-appreciated role in psychopathology (Candini et al, 2017;Noel et al, 2017). Thus, the results reported here suggest that function fitting coupled with immersion in a realistic environment and the presentation of multiple cues of information pertaining to the external environment may be best suited for future individual differences studies of PPS.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests that IPS is modulated by higher order psychological and social factors concerning personality characteristics 2 , perception of social context 36 , and the attitude toward the interacting parts 5, 6, 9 . In the current study, in light of recent evidence emphasizing the importance of one’s own body representation in modulating interpersonal attitude 1517, 20, 22 , we investigated whether a change in one’s own body representation can modify social IPS.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent studies have shown that children with autism spectrum disorder (ASD) have an altered IPS representation, preferring or larger 5, 6 or closer 51, 52 comfort-distances. People with social anxiety show an abnormal IPS too 8, 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are two additional reasons that support the goal of understanding interaction of persons with special abilities with large displays: (i) different kinds of interaction may impose a different distance of users from displays; (ii) the specific abilities of special persons may modulate their peripersonal space. In particular, children with ASD are known to be reluctant to interact with others at close distance, and their peripersonal space is significantly enlarged as compared to children with typical development [10].…”
Section: Introductionmentioning
confidence: 99%